Antioxidant Activity of Purple Colored Fruit Extracts - Dudek, Megan (My University, 2012)
This study tested the antioxidant activity of extracts from highly purple colored fruits, such as pomegranate, pokeweed, purple corn, purple potato, etc. The research investigated to see if the purple colored substance, which contained a variety of anthocyanin compounds plus other unknown compounds, would have antioxidant properties.
Color poster with text, diagrams, graphs, and tables.
Keywords: Antioxidants; Fruit--composition; Posters